PENGARUH DANA PIHAK KETIGA DAN LOAN TO DEPOSIT RATIO TERHADAP PENYALURAN KREDIT (Studi kasus pada PT Bank Republik Indonesia (Persero) Tbk periode tahun 2007 â€“ 2016) - Ali, Muhammad (Jurnal Riset Akuntansi dan Keuangan, 2018)
This study aims the effect Third Party Funds (TPF) and Loan to Deposit Ratio (LDR) to the total of loans. Bank Rakyat Indonesia Co., Ltd is used in this study for the object in period 2007-2016. The method of this research is descriptive and associative method with technique analysis that used is multiple regression analysis. Based on t test with SPSS 20, TPF partially a positive and significant effect on the total of loans. LDR also partially a positive and significant effect on the total of loans. Based on F test with SPSS 20, TPF and LDR simultaneously have significant influence on the total of loans.Â Keywords : Third Party Funds, Loan to Deposit Ratio (LDR), total of loans